Dampak Penerapan Coercive Power dan Pemberian Sanksi di dalam Pembalajaran Akademik Mahasiswa Santri - Hatoguan Hutahaean, Erik Saut; Pertiwi, Yuarini Wahyu; Thamrin, Djuni (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
The phenomenon of santri students in Indonesia encompasses various aspects that reflect the influence of pesantren education and Islamic values on their experiences and identities in the university environment. Santri students in Indonesia, like students in general, may also encounter various challenges during their university studies. However, there are some issues that are more commonly experienced by santri students, particularly related to their educational backgrounds in pesantren and their religious experiences. A total of 186 santri students were involved in filling out questionnaires measuring academic commitment, the application of coercive power, the imposition of sanctions, and compliance. Based on mediation analysis, the results indicate that the application of coercive power and the imposition of sanctions can serve as appropriate mediators in bridging the influence of academic commitment to compliance. Compliance among santri students is not solely a result of their academic commitment because the level of compliance can be shaped by the university's application of coercive power and the imposition of sanctions for students who violate rules.